Effect of adding a gonadotropin-releasing-hormone treatment at the beginning and a second prostaglandin F-2 alpha treatment at the end of an estradiol-based protocol for timed artificial insemination in lactating dairy cows during cool or hot seasons of the year - Pereira, M. H. C. [UNESP]; Wiltbank, M. C.; Barbosa, L. F. S. P. [UNESP]; Costa, W. M. [UNESP]; Carvalho, M. A. P.; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2015)
Our hypothesis was that fertility could be increased in a timed artificial insemination (TAI) protocol based on estradiol (E2) and progesterone (P4) by combining GnRH with E2-benzoate at the start of the protocol to increase circulating P4 during preovulatory follicle development and by using 2 prostaglandin F-2 alpha (PGF) treatments at the end to decrease P4 near TAI. Lactating Holstein cows (n = 1,808) were randomly assigned during the cool or hot season of the year to receive TAI (d 0) following 1 of 3 treatments: (1) control: controlled internal drug-release insert + 2 mg of E2-benzoate on d -11, PGF on d -4, controlled internal drug-release insert withdrawal + 1.0 mg of E2-cypionate on d -2, and TAI on d 0; (2) 2PGF: identical to control protocol with addition of a second PGF treatment on d -2; (3) GnRH: identical to 2PGF protocol with addition of a 100-mu g GnRH treatment on d -11. Pregnancy diagnoses were performed on d 32 and 60 after TAI. Season had major effects on many reproductive measures, with cool season greater than hot season in percentage of cows with corpus luteum (CL) at PGF (62.9 vs. 56.2%), ovulatory follicle diameter (15.7 vs. 14.8 mm), expression of estrus (86.7 vs. 79.9%), ovulation following the protocol (89.7 vs. 84.3%), and pregnancies per artificial insemination (P/AI; 45.4 vs. 21.4%). The GnRH protocol increased percentage of cows with CL (control = 56.9%; 2PGF = 55.8%; GnRH = 70.5%) and P4 at PGF (control = 3.28 +/- 0.22; 2PGF = 3.35 +/- 0.22; GnRH = 3.70 +/- 0.21 ng/mL), compared with control and 2PGF protocols. The GnRH protocol increased P/AI at the pregnancy diagnosis at 32 d [37.3% (219/595)] and 60 d [31% (179/595)] after TAI, compared with control 30.0% (177/604); 25.1% (145/604)], with intermediate results with 2PGF protocol [33.2% (196/609); 28.0% (164/609)]. The positive effects of GnRH treatment on P/AI were only detected during the cool season (GnRH = 50.9%; 2PGF = 44.2%; control = 41.0%) and not during the hot season. In addition, the effect of GnRH was only observed in cows with low P4 (< 3 ng/mL) at the start of the protocol and not in cows that began the protocol with high P4. Furthermore, presence of CL at PGF interacted with follicle diameter such that cows with a CL at PGF had greater P/AI if they ovulated larger rather than smaller follicles near TAI. Thus, fertility to TAI can be improved by inducing ovulation at the beginning of an E2/P4-based protocol using GnRH treatment, particularly during the cool season of the year and in cows with low P4 at the start of the protocol.
Keywords: gonadotropin-releasing hormone; follicle diameter; progesterone